Fotografia em processos de criação nas artes visuais - Moreira, Felipe Raizer (2013)
The main objective of this work is to study contemporary photography in their new media within a framework that involves: poetic projects of artists who seek to transgress the conventional photography (its concepts and structures), in the time of digital images, which has expanded the concept photography to new frontiers. We will see that the image manipulation occurs by procedures that move between different media, ensuring endless possibilities for intervention from the photographer in their production. We hypothesized that the evolution of the techniques of visual representation, their movements and conceptual clashes, allied to technological appliances and tools are changing the photographic paradigm, in this sense that the photographic image is shown to be less committed to the faithful representation of "reality" and more conducive to the expression of ideas. The corpus of research involves the creative work of artists Elaine Tedesco, Lucio Carvalho, João Penoni and my own visual work, taken as examples of pictures of perspective here pointed out. We seek theoretical support in main theories that analyze the current photographic paradigm, with Villém Flusser and Lucia Santaella, and other conceptual proposals for contemporary photography with Arlindo Machado, Andreas Muller Pohle and Rubens Fernandes. Another basic one offered by the analysis of creation processes in Cecilia Almeida Salles theory. The research is done by raising pertinent reflections on the convergence of languages, state paradigm that defines photography, creative processes between media, use of technical methodologies for the production of visual sense, and the breaking of traditional photography code. We will study here a image that might need another name other than photography: image metamorphosis, aesthetic of possibilities that develops in several stages and processes, towards complexity